Triangular coronally advanced flap: Conventional versus Microsurgery - Nashra Kareem; Jaideep Mahendra; Kanakamedala Anil Kumar (Wolters Kluwer Medknow Publications, 2018)
Several surgical techniques including pedicle flaps and free soft-tissue grafts have been indicated for the treatment of gingival recession defects with different success rates. Localized gingival recessions can be managed with various root coverage procedures, more specifically, using the coronally advanced flap with distinct designs. Predictable and consistent periodontal plastic surgical results can be achieved by using microsurgical instruments. Periodontal microsurgery involves the use of magnifying devices, microsurgical instruments, and materials in existing basic surgical techniques. It offers definitive advantages in terms of predictability, postoperative morbidity, and patient approval. This case report aims at comparing the modified approach with a triangular type of coronally advanced flap, using conventional and microsurgical approach, for treating bilateral isolated Miller's class I defect in both the maxillary canines by a split-mouth design.